Postsynthetic Modification of Metal−Organic Frameworks for Photocatalytic Applications. Issue 5 (9th February 2022) - Lin, Huaxing; Xu, You; Wang, Bing; Li, Dong-Sheng; Zhou, Tianhua; Zhang, Jian
Abstract : Metal−organic frameworks (MOFs) are a new class of porous, crystalline materials with promising applications in the fields of energy and environment. Postsynthetic modification (PSM) approaches are shown to be powerful techniques to introduce new functionalities to parent frameworks. PSM methods to functionalize MOFs can be divided into four main categories based on their unique structures: covalent modification, coordinative transformation, encapsulation, and hybridization with other compounds. These approaches are proven to be an important tool for increasing structural stability and introducing desired properties, which expand the applications of MOFs. This review focuses on the current advancements of four PSM methods to construct functionalized MOFs for photocatalytic applications in water splitting, CO2 reduction, organic transformation, and degradation of water pollutants. The challenge and perspectives on PSM of MOFs for photocatalysis are also discussed. Abstract : The current advancements and challenges of the postsynthetic modification method to construct metal−organic frameworks for photocatalysis are outlined and discussed.